2018
DOI: 10.1101/318287
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Overexpression of the vascular brassinosteroid receptor BRL3 confers drought resistance without penalizing plant growth

Abstract: Drought represents a major threat to food security. Mechanistic data describing plant responses to drought have been studied extensively and genes conferring drought resistance have been introduced into crop plants. However, plants with enhanced drought resistance usually display lower growth, highlighting the need for strategies to uncouple drought resistance from growth. Here, we show that overexpression of BRL3, a vascular-enriched member of the brassinosteroid receptor family, can confer drought stress tol… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
53
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(57 citation statements)
references
References 71 publications
(26 reference statements)
4
53
0
Order By: Relevance
“…It is becoming increasingly evident that the BR pathway does not represent a linear signaling pathway that operates in isolation, but rather that BRs undergo crosstalk with multiple other hormones and stress responses (Nolan et al, 2017a). Moreover, BR signaling varies among different cells and tissues, which can be manipulated to improve plant growth and stress responses (Fàbregas et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…It is becoming increasingly evident that the BR pathway does not represent a linear signaling pathway that operates in isolation, but rather that BRs undergo crosstalk with multiple other hormones and stress responses (Nolan et al, 2017a). Moreover, BR signaling varies among different cells and tissues, which can be manipulated to improve plant growth and stress responses (Fàbregas et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…This appears to be the case for the BR signaling pathway operating through BRI1 to downstream BES1 and BZR1 TFs (Chen et al, 2017;Nolan et al, 2017b;Ye et al, 2017). However, overexpression of the vascular BR receptor BRL3 promotes drought responses without penalizing growth (Fàbregas et al, 2018).…”
Section: Br and Aba Pathways Antagonize One Anothermentioning
confidence: 97%
See 2 more Smart Citations
“…Recently, it was reported that the apoplastic proton extrusion in root tips is influenced by brassinosteroids (BRs) receptor BR-INSENSITIVE1 (BRI1), which is also crucial for the hydrotropic root response in Arabidopsis [27,28]. Whereas loss-of-function mutations in the ubiquitously expressed BRI1 receptor leads to drought resistance at the expense of growth, overexpression of theBRL3 receptor confers drought tolerance without penalizing overall growth [29]. Hence, BRs signaling links the hydrotropic root response with drought resistance.…”
Section: Introductionmentioning
confidence: 99%